FAKTOR - FAKTOR YANG MEMPENGARUHI KEJADIAN ANEMIA PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS MEDAN JOHOR TAHUN 2019 - PLORA NOVITA FEBRINA SINAGA (JURNAL ILMIAH KOHESI, 2020)
Normal hemoglobin levels generally differ in both men and women. According to the WHO normal hemoglobin levels in adultwomen 12.0 gr/dl, adult males 13.0 gr/dl, pregnant women 11.0 gr/dl. The prevalence of anemia is estimated to be about 14percent in developed countries and 51 percent of developing countries (Vanamala, et al, 2018). In 2011, the prevalence ofanemia in pregnant women was 29 percent and pregnant women aged 15-49 were 38 percent. The World HealthOrganization (WHO) is targeting a 50 percent decrease in the prevalence of anemia in WUS by 2025 (WHA, 2015). Anemiain pregnant women is a problem that needs to be taken seriously, because it has a bad impact on the fetus, the laborprocess and postpartum period. Fe tablets have been given to prevent anemia but the prevalence of anemia until now is stillhigh. Maternal Mortality Rate (AKI) and Infant Mortality Rate (AKB). Morbidity and perinatal maternal mortality are still high indeveloping countries. According to a 2014 World Health Organization (WHO) report, the world maternal mortality rate is289,000. The number of maternal deaths decreased from 385 in 1990 to 216 in 2015 per 100,000 live births. The WorldHealth Organization (WHO) estimates 800 women die every day from pregnancy complications and the birth process. About99% of all maternal deaths occur in developing countries. About 80% of maternal deaths are due to increased complicationsduring pregnancy, childbirth and after childbirth (WHO, 2014).